Problem Based Learning (PBL) Based on Multiculturalism at SMA Tonasa 1 Pangkep - Suwarni Jayanti; Nurrahmah Nurrahmah; Ma’rifah Ma'rifah; Andi Azis; Alimuddin Alimuddin; Muh. Natsir (Early Publishing, 2026)
This research aims to analyze the implementation of multicultural-based Problem Based Learning (PBL) in the 11th grade at SMA Tonasa 1 Pangkep, its impact on students, as well as the supporting and inhibiting factors. This research uses a qualitative approach with a case study design. Data were obtained thru observations, interviews with teachers and school principals, as well as learning documentation. The research results show that the implementation of multicultural-based PBL proceeds gradually and contextually by utilizing problems that are close to students' social experiences. This model encourages students to be more active, enhances critical thinking skills, learning participation, tolerance, empathy, communication, and appreciation of differences. Conceptually, multicultural-based PBL contributes to the formation of active, inclusive, and humanistic learning, while theologically it is grounded in the values of the Qur'an, specifically Qs. Al-Mumtahanah verse 8 and Qs. Al-Hujurat verse 13. Supporting factors for the implementation of this model include teacher commitment, the formation of heterogeneous groups, contextual problem design, and learning device support. The inhibiting factors include time constraints, curriculum load, limited facilities, and differences in students' communication skills. This study concludes that multicultural-based PBL has the potential to enhance students' academic competence as well as their social attitudes if supported by teacher facilitation, an inclusive school environment, and parental involvement.